A U.S.-Chinese Comparison of Affectionate Communication in Parent-Child Relationships. Issue 4 (1st October 2016) - Zhang, Qin; Wills, Maggie
Abstract : Affectionate communication is central to the maintenance of relational closeness, but it is also subject to relational, contextual, and cultural factors. This study was designed to examine the cultural effects on affectionate communication in parent-child relationships in the United States and China. Results indicated that Chinese fathers and mothers expressed less verbal, nonverbal, and supportive affection to their children than American parents. Both Chinese and American parents expressed affection to their children more through supportive behaviors than through verbal and nonverbal behaviors. In both cultures, mothers engaged in more verbal, nonverbal, and supportive affection with their children than fathers.